Prediction of the soft-tissue facial morphology matrices in a European population, a Geometric Morphometric study using Cone- Beam Computed Tomography. - Ridel, A.F. (Alison) (University of Pretoria, 2024)
Dissertation (MSc (Anatomy))--University of Pretoria, 2023.